Public attitudes towards automated external defibrillators: results of a survey in the Australian general population - Kovoor, Joshua G.; Marschner, Simone; Amarasekera, Anjalee; Nageswaran, Meera; Page, Gregory J.; Chow, Clara K.; Thiagalingam, Aravinda; Kovoor, Pramesh (Frontiers in Cardiovascular Medicine, 2023)
Background Swift defibrillation by lay responders using automated external defibrillators (AEDs) increases survival in out-of-hospital cardiac arrest (OHCA). This study evaluated newly-designed yellow-red versus commonly-used green-white signage for AEDs and cabinets, and gauged public attitudes to using AEDs during OHCA. Methods New yellow-red signage was designed to enable easy identification of AEDs and cabinets. A prospective, cross-sectional study of the Australian public was conducted using an electronic, anonymised questionnaire between November 2021 and June 2022. The validated net-promoter score (NPS) investigated public engagement with the signage. Likert scales and binary comparisons evaluated preference, comfort and likelihood of using AEDs for OHCA. Results: The yellow-red signage for AED and cabinet were preferred by 73.0% and 88% respectively over the green-white counterparts. Only 32% were uncomfortable in using AEDs and only 19% indicated low likelihood of using AEDs in OHCA. Conclusion: Majority of Australian public surveyed preferred yellow-red over green-white signage for AED and cabinet and indicated comfort and likelihood of using AEDs in OHCA. Steps are necessary to standardise yellow-red signage of AED and cabinet and enable wide-spread availability of AEDs for public access defibrillation.